Effect of hydrogen concentration on the explosion severity in a closed vessel - Mohd Aidil, Awaluddin (2016)
Hydrogen gas can be produced from steam reforming natural gas, and steam gasification process. Hydrogen is widely used for producing ammonia for fertilizer, petroleum refining, glass purification and many others application. Through the rapid discoveries for the hydrogen production, this lead to the severity of hydrogen explosion phenomenon and tough safety precautions in term of quantitative and qualitative were required. Thus, this study will discover the severity limit of hydrogen explosion. The objectives in this study are to know the maximum rate of pressure rise (dp/dt)max, maximum explosion pressure (Pmax), and to study the explosion in different vessel shapes. Pure hydrogen (99.9%) was used as the fuel and mix with air. The experiment were conducted in a 20-L spherical bomb with hydrogen content in air at 30% v/v and different equivalence ratio from Ø = 0.4 to 1 in Combustion Laboratory, Faculty of Chemical Engineering, Universiti Malaysia Pahang with two igniters of 10kJ at the centre of the vessel. The experiment was repeated three times to get the fit result. From the result obtained the maximum explosion pressure, Pmax and rate of pressure rise, dP/dt increase with increase of hydrogen concentration in air. This is due to the increase amount of fuel and more chemical reaction happened during the explosion. Higher explosion parameters were happened at stoichiometry concentration or at equivalence ratio 1 with Pmax 5.4 bar and dP/dt 1410.3 bar/s. In comparison between spherical and 2-in pipe and 4-in pipe, the 2-in pipe has higher explosion pressure of 9.1 bar at equivalence ratio 1. This is due to the quenching effect in larger diameter (0.1 m in 4-in pipe and 0.34 m in spherical vessel) plays a significant role on the explosion pressure development. Different result obtained on rate of pressure rise, dP/dt in these three vessel shapes. Explosion in the spherical vessel tends to have higher value of dP/dt at 1410.3 bar/s. High dP/dt means amount of burning rate and pressure generation to be released from the explosion is has severe condition. Thus this concluded that hydrogen-air mixture explosion is more severe in spherical vessel compare to explosion in cylindrical vessel.